Verification of on-demand medical device networks - Dingler Max; Dietz Christian; Lüth Tim (Current Directions in Biomedical Engineering, 2017)
We propose a novel method for the automated formal analysis of on-demand medical device networks communicating via an open communication protocol. The resulting toolbox aims at assisting operators of cross-vendor medical device networks in the complex process of conformity assessment. The method is based on the notion of timed, extended finite automata and employs existent TCTL model checking techniques by use of MATLAB and UPPAAL. We evaluate our methodology in a real-life application similar to a user experience published by the U.S. Food and Drug Admninistration. The method revealed a flaw in the connector design for the Surgical Real Time Bus of the OR.Net project.